The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1093/gerona/61.5.488
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Changes in Body Weight Exert Independent and Site-Specific Effects on Bone in Postmenopausal Women Exercising for 1 Year

Abstract: The negative impact of depressive symptoms on BMD in this population of postmenopausal women was independent of body weight or other behavioral factors such as calcium compliance or exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 27 publications
0
38
1
1
Order By: Relevance
“…37 A recent 1-year longitudinal study of 320 postmenopausal white women (average age 56 years) did not observe an association between depressive symptoms and BMD loss at the more trabecular spine. 15 A second study including older white women (average age 76, n=4,177) reported an inverse relationship between depressive symptoms and total hip BMD. 16 Both studies reported an association between depressive symptoms and bone loss at the more cortical femoral neck region, but not at the trochanter.…”
Section: Discussion Bmd Changementioning
confidence: 98%
See 3 more Smart Citations
“…37 A recent 1-year longitudinal study of 320 postmenopausal white women (average age 56 years) did not observe an association between depressive symptoms and BMD loss at the more trabecular spine. 15 A second study including older white women (average age 76, n=4,177) reported an inverse relationship between depressive symptoms and total hip BMD. 16 Both studies reported an association between depressive symptoms and bone loss at the more cortical femoral neck region, but not at the trochanter.…”
Section: Discussion Bmd Changementioning
confidence: 98%
“…However, another study of younger women with low levels of depressive symptoms excluded women with low BMD and still reported an association between femoral neck BMD and Beck Depression Inventory score (BDI). 15 These authors repeated their analysis replacing the BDI with the Burnam measure and found persistence of the association with changes in femoral neck BMD (p=0.09). Finally, depression may be associated with study withdrawal or with incomplete information.…”
Section: Fracturementioning
confidence: 95%
See 2 more Smart Citations
“…Fourteen articles met the eligibility criteria and were included in the meta-analysis [7][8][9][10][11][12][13][14][17][18][19][20][21][22]. When two or more publications were based on the same study population and reported the same outcomes, the report with the largest number of participants was selected.…”
Section: Study Selectionmentioning
confidence: 99%